Assessment of knowledge, attitude and practices regarding dengue among the general population of Goa - Cardozo, Manfred F.; Balaji, Ezekhil; Francis, Ajish; Dias, Amit; Lydia Dias, (International Journal Of Community Medicine And Public Health, 2023)
Background: Dengue is a major health problem in India. The state of Goa has seen a rise in the incidence of Dengue. The study was conducted to understand the knowledge, attitude and practices (KAP) of the people regarding this disease. Methods: This was a cross sectional descriptive study conducted on a sample of participants of the state of Goa. Data on demographic characteristics and KAP was obtained from participants through Google forms. Results: A large number of participants had adequate knowledge of the source of infection and even modes of transmission. Knowledge of symptomatology and treatment was seen to be inadequate. Symptoms such as pain behind the eye and abdominal pain were known by less than 33% of the population. 61.84% were aware that dengue is transmitted through Aedes mosquito. Knowledge of symptoms and the vector transmitting dengue virus was least among the non-student participants. 44.7% of the participants opined that papaya leaves are beneficial for treatment with a higher proportion among the non-student population. Knowledge of the complications of dengue such as dengue haemorrhagic fever was reported by 56.6% of the population while dengue shock syndrome was reported by 32.3% of the population. Conclusions: Findings indicate there is lesser knowledge of symptomatology and epidemiology of dengue among the non-student participants compared to the student participants. Educational and health programmes are needed to increase knowledge among the general population, campaigns specifically targeting the non-student population are required.